Clinical relevance of molecular subgrouping of gliomatosis cerebri per 2016 WHO classification: a clinicopathological study of 89 cases. (7th October 2019) - Kwon, Mi Jung; Kang, So Young; Cho, Haeyon; Lee, Jung Il; Kim, Sung Tae; Suh, Yeon‐Lim
Abstract: The extremely invasive phenotypes and genotypes related to progression of gliomatosis cerebri (GC) remain unclear although GC has been removed as an independent entity from the 2016 WHO classification. Hence, categorization of GC under the current WHO molecular classification is essential, and the molecular subgroups that might contribute to GC progression should be compared with the histopathological differences between initial and new lesions identified during follow‐up. Analyses of IDH1/2 and TERTp mutations and 1p/19q co‐deletion, and immunohistochemistry of IDH1‐R132H, ATRX, p53 and galectin‐3 were performed. Anaplastic astrocytoma, IDH‐wildtype (AA‐IDHwt) was the common molecular subgroup (52.8%), followed by diffuse astrocytoma, IDH‐wildtype (DA‐IDHwt) and AA, IDH‐mutant (AA‐IDHmt) (each 16.9%), DA‐IDHmt (7.9%), glioblastoma (GBM)‐IDHwt (3.3%) and GBM‐IDHmt (2.2%). Approximately 92% of the AA‐IDHwt lesions progressed to histologically confirmed GBM in the newly enhanced lesions harboring the TERTp mutation and expressing galectin‐3. Similar to primary GBMs, GC‐related GBMs that progressed from the IDHwt subgroups showed microvascular proliferation, palisading necrosis or thrombotic occlusion, implying that a subset of IDHwt subgroups may evolve to overt GBM. Molecular subgrouping did not provide the perfect prediction for the survival of GC patients. The AA‐IDHwt group showed worse overall and progression‐free survival (PFS) than the AA‐IDHmt group. Biopsy plus radiotherapy, chemotherapy and temozolomide treatment for DA‐IDHwt, and resection plus radiotherapy and temozolomide treatment for AA‐IDHwt prolonged PFS. In conclusions, majority of GC was of the AA‐IDHwt subgroup, which progressed to GBM. Molecular subgroups may assist in the selection of treatment modalities, because "GC pattern" still remains as a special growth of gliomas in WHO 2016 classification without established treatment guideline.